2014
DOI: 10.14814/phy2.12058
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitors act from the extracellular surface of the cell membrane

Abstract: SGLT2 inhibitors are a new class of drugs that have been recently developed to treat type II diabetes. They lower glucose levels by inhibiting the renal Na+/glucose cotransporter SGLT2, thereby increasing the amount of glucose excreted in the urine. Pharmacodynamics studies have raised questions about how these inhibitors reach SGLT2 in the brush border membrane of the S1 and S2 segments of the renal proximal tubule: are these drugs filtered by the glomerulus and act extracellularly, or do they enter the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 23 publications
3
46
0
3
Order By: Relevance
“…This is consistent with (1) the free glomerular filtration of the nonspecific SGLT inhibitor phlorizin, the phlorizin inhibition of glucose reabsorption, and the displacement of [ 3 H] phlorizin binding by excess cold phlorizin 18 as well as (2) the observation that SGLT2 inhibitors only block glucose transport when present on the outside surface of the cell. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with (1) the free glomerular filtration of the nonspecific SGLT inhibitor phlorizin, the phlorizin inhibition of glucose reabsorption, and the displacement of [ 3 H] phlorizin binding by excess cold phlorizin 18 as well as (2) the observation that SGLT2 inhibitors only block glucose transport when present on the outside surface of the cell. 19 …”
Section: Discussionmentioning
confidence: 99%
“…28 Serial blood samples (approximately 40 ml) were manually drawn from the femoral artery and renal vein. The first nine samples were collected within the first 2 minutes, and the rest of the blood samples was collected at 10,19,22,25,30,40, and 58 minutes post-tracer injection and placed in heparinized microhematocrit tubes (Fisherbrand, Houston, TX). Blood samples were immediately centrifuged to separate the plasma from the cells.…”
Section: F-dapa In Rat Plasmamentioning
confidence: 99%
“…There is currently no experimental evidence for the sidedness of the action of clinically used selective SGLT2 inhibitors. In the study using TA-3404, a compound with a canagliflozin-related structure, it has been suggested that the SGLT2 inhibition occurs from the extracellular side (Ghezzi et al, 2014). In addition, we speculated that canagliflozin is not only an inhibitor of SGLT2, but also a substrate for SGLT2, and that SGLT2-mediated active transport, at least in part, explains the low urinary excretion rate observed with the use of canagliflozin.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, the aglucones of Pz and high affinity SGLT2 inhibitor dapagliflozin e which provides a reference point for comparison with other structurally related hSGLT2 inhibitors e weakly inhibit both hSGLT1 and hSGLT2 suggesting that aglucone affects the binding affinity of the entire inhibitor. Furthermore, changing the sugar moiety of dapagliflozin from glucose to galactose reduces its affinity to both SGLTs indicating a flexible sugar binding to the glucose site [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another high affinity analog of Pz, canagliflozin, has been shown to be a highly effective and selective inhibitor of human SGLT2 [13]. TA-3404 is a derivative of canagliflozin [14] which has a several 100s fold much higher selectivity for SGLT2 over SGLT1 [13].…”
Section: Introductionmentioning
confidence: 99%